Selected Decisions (12th Ed). (Selected Decisions; Issue, Year, 1986)
This paper discusses several IMF's selected decisions of the Executive Board and selected documents. The Executive Directors of the IMF interpret the Articles of Agreement to mean that authority to use the resources of the IMF is limited to use in accordance with its purposes to give temporary assistance in financing balance-of-payments deficits on current account for monetary stabilization operations. This volume is the Twelfth Issue of Selected Decisions of the IMF and Selected Documents. It contains the decisions, interpretations, and resolutions of the Executive Board and the Board of Governors of the IMF to which frequent reference is made in the current activities of the IMF. In addition, the volume contains certain documents relating to the IMF and the United Nations. With few exceptions, the decisions are of a general nature and relate to certain obligations, policies, and procedures under the Articles of Agreement. This issue contains most of the decisions published in the Eleventh Issue that remain in effect, as well as new general decisions adopted after the publication of the Eleventh Issue. Decisions of the IMF that are incorporated in the Rules and Regulations are not reproduced in this volume.